Relationship between JAK2V617F mutation, allele burden and coagulation function in Ph-negative myeloproliferative neoplasms. Issue 6 (3rd July 2017) - Hu, Linhui; Pu, Lianfang; Ding, Yangyang; Li, Manman; Cabanero, Michael; Xie, Jingxin; Zhou, Dejun; Yang, Dongdong; Zhang, Cui; Wang, Huiping; Zhai, Zhimin; Ru, Xiang; et al.
ABSTRACT: Objectives: Our aim was to explore the relationship between JAK2V617F mutation allele burden and hematological parameters especially in coagulation function in Chinese population. Methods: This study included 133 Ph-negative myeloproliferative neoplasms (MPNs) patients between 2013 and 2016. All the clinical and experimental data of patients were collected at the time of the diagnosis without any prior treatment, including blood parameters, coagulation function, splenomegaly, vascular events and chromosome karyotype. PCR and qPCR were used to detect JAK2V617F mutation and JAK2V617F mutation allele burden. Results: In polycythemia vera patients, a positive correlation between the allele burden of JAK2V617F mutation and PLT counts was found; in essential thrombocythemia (ET) patients, WBC counts, RBC counts, HB, and HCT were higher in mutated patients than in wild-type patients. Furthermore, PT-INR was higher in ET and PMF mutated patients. In addition, a positive correlation between the allele burden of JAK2V617F mutation and activated partial thromboplastin time (APTT) was observed in JAK2V617F mutated ET patients. Conclusions: Higher hematologic parameters including counts of WBC, RBC, and PLT are closely associated with JAK2V617F mutation and its burden in Ph-negative MPNs; importantly, PT-INR, APTT are also related to JAK2V617F mutation and allele burden. Thus, our data indicate that JAK2V617F mutation allele burden might not only represent the burden of MPN but also alter the coagulation function.